Relative frequency of immature CD34+/CD90+ subset in peripheral blood following mobilization correlates closely and inversely with the absolute count of harvested stem cells in multiple myeloma patients - Balint, Bela; Stanojević, Ivan; Todorović, Milena; Stamatović, Dragana; Pavlović, Mirjana; Vojvodić, Danilo (Vojnosanitetski pregled, 2017)
Background/Aim. Stem cells (SCs) guarantee complete/long-term bone marrow (BM) repopulation after SC-transplants. The aim of the study was to evaluate absolute count of total SCs (determined by ISHAGE-sequential-gating protocol – SCish) and relative frequency of immature CD34+/CD90+ (CD90+SCish) subset in peripheral blood (PB) as predictive factors of mobilization and apheresis product (AP) quality. Methods. Mobilization included chemotherapy and granulocyte-growth-factor (G-CSF). Harvesting was performed by Spectra-Optia-IDL-system. The SCsish were determined as a constitutional part of CD34+ cells in the “stem-cell-region” using FC-500 flow-cytometer. In this study, the original ISHAGE-sequential-gating protocol was modified by introduction of anti-CD90-PE monoclonal-antibody into the analysis of CD90 expression on SCish (CD90+SCish). The results were presented as a percentage of SCish per nucleated-cell count, absolute SCish count in μL of the PB or the AP, percentage of the CD90+SCish expressed to SCish and absolute CD90+SCish count in μL of the PB or the AP. Results. The absolute count of total SCish and CD90+SCish was significantly higher (p = 0.0007 and p = 0.0266, respectively) in the AP than in the PB samples. The CD90+SCish/total SCish indexes from PB were higher than indexes from the AP (p = 0.039). The relative frequency of CD90+SCish showed a highly significant inverse correlation with the absolute count of total SCish in both, the PB and AP (p = 0.0003 and p = 0.0013 respectively). The relative frequency of CD90+SCish from the PB also showed a significant (p = 0.0002) inverse relationship with total SCish count in the AP. Patients with less than 10% CD90+SCish in the PB had evidently higher (p = 0.0025) total SCish count in the AP. Conclusion. We speculate that lower CD90+SCish yield in the AP is not a consequence of an inferior collection efficacy, but most likely a result of several still not fully resolved immature SC cytomorphological/biophysical features. Therefore, following the mobilization by chemotherapy G-CSF, some logical questions appear – whether we should follow the absolute count of total SCish, or, whether we should test for relative frequency of CD90+SCish prior to harvesting. To reach the final conclusions, it is essential to conduct further controlled and larger investigations concerning the correlation of circulating and harvested SCs with patients’ hematopoietic recovery.